Karakteristik wirausaha, modal usaha dan kecanggihan teknologi terhadap kinerja UMKM di masa pandemi Covid-19 - Mukoffi, Ahmad; As’adi, As’adi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This research aims to analyze the influence of entrepreneurial characteristics, venture capital, and technological sophistication on the performance of MSMEs. The data collection method used in this study was a questionnaire. The number of respondents as the research sample was 302 MSME owners in Pasuruan Regency. The analysis technique used is multiple regression analysis. The findings of this study indicate that entrepreneurial characteristics have a significant positive effect on the performance of MSMEs, as well as venture capital which has a significant positive effect on performance. Meanwhile, technological sophistication shows that it does not have a positive effect on the performance of MSMEs Â